EXTERNAL INVESTMENTS AND THEIR ECONOMIC CONTROL IN THE MANAGEMENT OF ENTERPRISES OF TERRITORIAL COMMUNITIES (INNOVATIVE ECONOMY, 2024)
Balaniuk I.F., Lyutyy Y.V. EXTERNAL INVESTMENTS AND THEIR ECONOMIC CONTROL IN THE MANAGEMENT OF ENTERPRISES OF TERRITORIAL COMMUNITIESPurpose. The aim of the article is to define and substantiate the essence of external investments and various forms of their implementation for the economic development of enterprises of territorial communities.Methodology of research. The methodological basis of the research is the scientific works of foreign and domestic scientists on the issues of foreign investments and forms of their implementation. General scientific and specific methods were used to achieve the set goals, such as: dialectical method of scientific knowledge – to consider the essence of foreign investments; analysis and synthesis – to clarify the relationships between the elements of the mechanism; graphic – for a visual representation of the proposed measures; abstract and logical – for forming research conclusions and proposals.Findings. The essence of foreign investments is analysed. It has been established that investment attraction is one of the key factors in the management of enterprises of territorial communities. Key elements of foreign investments and significant aspects related to their essence are highlighted.Originality. A comprehensive understanding of the key aspects of attracting foreign investments and their impact on the management of enterprises of territorial communities has been offered. The study highlights the interaction of elements that determine the efficiency of the investment process and its role in creating a favourable economic environment.Practical value. The conclusions of the study have practical significance for local authorities and interested parties aimed at managing enterprises of territorial communities. In particular, the need for targeted investments in infrastructure, support of small and medium-sized businesses, regulation of human capital development, tourism development and innovation support is indicated. Integrating these elements into development strategies is a key to create an enabling environment for business development, contributing to economic stability and reducing inequality between them.Key words: investments, external investments, internal investments, risks, investment activity, enterprise management, economic control, territorial communities.
Keywords: investments; external investments; internal investments; risks; investment activity; enterprise management; economic control; territorial communities.